Passive buoyant tracers in the ocean surface boundary layer: 2. Observations and simulations of microplastic marine debris. Issue 11 (20th November 2015) - Brunner, K.; Kukulka, T.; Proskurowski, G.; Law, K. L.
Abstract: This paper is the second of a two‐part series that investigates passive buoyant tracers in the ocean surface boundary layer (OSBL). The first part examines the influence of equilibrium wind‐waves on vertical tracer distributions, based on large eddy simulations (LESs) of the wave‐averaged Navier‐Stokes equation. Motivated by observations of buoyant microplastic marine debris (MPMD), this study applies the LES model and the parametric one‐dimensional column model from part one to examine the vertical distributions of MPMD. MPMD is widely distributed in vast regions of the subtropical gyres and has emerged as a major open ocean pollutant whose distribution is subject to upper ocean turbulence. The models capture shear‐driven turbulence, Langmuir turbulence (LT), and enhanced turbulent kinetic energy input due to breaking waves (BWs). Model results are only consistent with observations of MPMD profiles and the relationship between surface concentrations and wind speed if LT effects are included. Neither BW nor shear‐driven turbulence is capable of deeply submerging MPMD, suggesting that the observed vertical MPMD distributions are a characteristic signature of wave‐driven LT. Thus, this study demonstrates that LT substantially increases turbulent transport in the OSBL, resulting in deep submergence of buoyant tracers. The parametric model is applied to 11 years of observations in the North Atlantic and North Pacific subtropical gyres to show that surface measurements substantially underestimate MPMD concentrations by a factor of 3–13. Key Points: Langmuir turbulence deeply submerges microplastic marine debris Microplastic marine debris content is underestimated by surface measurements Sea state and rise velocity are key parameters for marine debris distributions